ANALISIS KEPUASAN PENGGUNA TERHADAP ALGORITMA AI DALAM PERSONALISASI KONTEN PADA APLIKASI INSTAGRAM MENGGUNAKAN METODE EUCS - Callista Felisya; Felinsia Pung Handoko; Shella Marcelia; Dicky Pratama (LPPM Universitas Dhyana Pura, 2026)
As one of the popular platforms and often used by the general public, Instagram is a social media that is widely used by the public that allows us to post content, exchange content, and get information from the Artificial Intelligence (AI) algorithm. Based on the number of users who use the Instagram application, this study was conducted to provide a level of user satisfaction with the AI ​​algorithm in personalizing content presented by the Instagram application. The approach applied to assess the level of user satisfaction with the AI ​​algorithm is the End-User Computing Satisfaction (EUCS) Method. The data collection method appliedis the use of a questionnaire with a total of 18 questions distributed to 100 respondents who are active users of the Instagram a pplication. Based on the data collection obtained using EUCS, from a total of 5 hypotheses, there are 2 hypotheses that have a significant influence on the scale of user satisfaction and these variables are accuracy & timeliness variables. From the results of this hypothesis, it can be stated that the AI ​​algorithm in the Instagram application provides satisfaction to users in the context of content personalization accuracy and timeliness in presenting content, but the AI ​​algorithm has not made a significant contribution to other aspects such as Content, Format and Ease of Use. The percentage obtained based on 5 hypothesis tests, 40% shows that the AI ​​algorithm has influenced user satisfaction, but the other 60% are content suitability, explore page accuracy, lack of application display, and user convenience in using the application that still needs to be returned by the application manager to provide a satisfying user experience. This study can be a basis for the Instagram application itself to improve the AI ​​algorithm in developing their application in order to provide comprehensive satisfaction to users.